Filtration and ingestion rates of Thalassiosira Weissflogii (Bacillariophyta) by Euterpina acutifrons Dana (Copepoda) - Lemos, Vanessa Oliveira; da Costa, Rauquírio Marinho; Pereira, Luci Cajueiro Carneiro (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
Short-term experiments were carried out to study the feeding performances of the copepod Euterpina acutifrons fed on Thalassiosira weissflogii. Four adult females of this species were sorted and transferred to 15 ml glass bottles filled with different dilutions of the diatom cultures to obtain cell concentrations of 7.5, 10.0, 12.5, 15.0, 17.5, 20.0, 22.5 and 25.0 x 103 cell.ml-1 (8 treatments, 3 replicates, 4 copepods/replicate). Initial and final cell concentrations of control and experimental bottles were determined using a Neubauer Chamber. Filtration and ingestion rates were measured thought 1 hour grazing trials performed under controlled laboratory conditions. Filtration rates of Euterpina acutifrons oscillated from 0.81 to 2.92 ml. copepod-1.h-1 and they significantly higher (p
Keywords: Feeding rates; Copepods; Diatoms